Effects of casein phosphopeptide amorphous calcium fluoride phosphate paste on white spot lesions and dental plaque after orthodontic treatment: a 3-month follow-up - Beerens, M. W.; Van Der Veen, M. H.; Van Beek, H.; Ten Cate, J. M. (European journal of oral sciences, 2010)
Beerens MW, van der Veen MH, van Beek H, ten Cate JM. Effects of casein phosphopeptide amorphous calcium fluoride phosphate paste on white spot lesions and dental plaque after orthodontic treatment: a 3‐month follow‐up. Eur J Oral Sci 2010; 118: 610–617. © 2010 Eur J Oral Sci The effects of casein phosphopeptide amorphous calcium fluoride phosphate (CPP‐ACFP) paste vs. control paste on the remineralization of white spot caries lesions and on plaque composition were tested in a double‐blind prospective randomized clinical trial. Fifty‐four orthodontic patients, with multiple white spot lesions observed upon the removal of fixed appliances, were followed up for 3 months. Subjects were included and randomly assigned to either CPP‐ACFP paste or control paste, for use supplementary to their normal oral hygiene. Caries regression was assessed on quantitative light‐induced fluorescence (QLF) images captured directly after debonding and 6 and 12 wk thereafter. The total counts and proportions of aciduric bacteria, Streptococcus mutans, and Lactobacillus spp. were measured in plaque samples obtained just before debonding, and 6 and 12 wk afterwards. A significant decrease in fluorescence loss was found with respect to baseline for both groups and no difference was found between groups. The size of the lesion area did not change significantly over time or between the groups. The percentages of aciduric bacteria and of S. mutans decreased from 47.4 to 38.1% and from 9.6 to 6.6%, respectively. No differences were found between groups. We observed no clinical advantage for use of the CPP‐ACFP paste supplementary to normal oral hygiene over the time span of 12 wk.